Die Tragödie Europas : Von der Krise des Jahres 1939 bis zum Angriff des nationalsozialistischen Deutschland auf die Sowjetunion - Möller, Horst 1943- HerausgeberIn; Čubarʹjan, Aleksandr Oganovič 1931- HerausgeberIn (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
The time between the Hitler-Stalin pact of 23 August 1939 and Germany`s invasion of the Soviet Union on 22 June 1941 remains a controversial period in European historiography. This volume presents the still multivalent interpretations of this first phase of World War II in German and Russian, as is the practice of the Historical Commission